ANALISIS TINGKAT KEPUASAN PEMILIK PROYEK TERHADAP KINERJA KONTRAKTOR PADA PEKERJAAN KONSTRUKSI DI KOTA AMBON - Gunther Hercules Sirait; Felix Taihuttu; Fauzan A Sangadji (Universitas Pendidikan Indonesia (UPI), 2023)
The contractor is a construction company that is key in implementing construction projects in the city of Ambon. The problem that occurs is the performance of contractor services in the city of Ambon is not optimal, so construction services with low quality and product quality are not in accordance with the expectations of the project owner. This study aims to determine the level of satisfaction of project owners on the quality of contractor performance in Ambon City and to evaluate this performance. Data analysis used the CSI (Customer Satisfaction Index) and IPA (Importance Performance Analysis) methods with the help of the SPSS 25 application. The variable attributes in this study totaled 36 attributes and the number of samples in this study were 100 respondents. From the analysis results obtained a CSI value of 0.803 with a satisfied classification so that it can be said that the construction project owner is satisfied with the contractor's performance on construction work in the city of Ambon. From the results of the IPA analysis it is known that the contractor's performance attributes which are the top priority for performance improvement include 8 attributes X1.5, X2.1, X3.6, X3.8, X4.3, X4.4,and X4.5.Keywords: Contractor Performance, Customer Satisfaction, Owner Satisfaction Index